The Potential of Metaverse Technology in Education as a Transformation of Learning Media in Indonesia - Pikir Wisnu Wijayanto; HM. Thamrin; Aceng Haetami; Sofyan Mustoip; Unan Yusmaniar Oktiawati (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to analyze the potential of metaverse technology in education to transform learning media in Indonesia. This research used a qualitative approach with descriptive methods. The type of research utilized library search. The secondary data comprised scientific papers indexed by Scopus and Sinta. The data analysis technique used in this research was thematic analysis. The results indicated that the technological metaverse perspective in education could present the best digital technology to support education in Indonesia. Implementing the metaverse in interactive learning media in Indonesia is divided into four types of simulation: lifelong, mirror world, augmented reality (AR), and virtual reality (VR). Opportunities within the metaverse as learning media in education include immersive interactive experiences, visualization, more economical risks and costs, unlimited space, and time, preventing academic violations, personalization, and promoting communication. Meanwhile, the possible challenges that will be faced are in the form of no boundaries for people involved in being lazy to move and other forms of neutral interaction.